2016
DOI: 10.1208/s12249-016-0491-5
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-In Vivo Evaluation of Novel Co-spray Dried Rifampicin Phospholipid Lipospheres for Oral Delivery

Abstract: Abstract. The objective of this study comprises of developing novel co-spray dried rifampicin phospholipid lipospheres (SDRPL) to investigate its influence on rifampicin solubility and oral bioavailability. Solid-state techniques were employed to characterize the liposphere formulation. SDRPL solubility was determined in distilled water. BACTEC 460TB System was employed to evaluate SDRPL antimycobacterial activity. The oral bioavailability of the lipospheres was evaluated in Sprague Dawley rats. Lipospheres ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Some studies revealed that MMAD of 1-5µm could be optimal range particles size for pulmonary delivery [48]. In our study, obtained results suggested that developed PLGA composites showed an acceptable range of MMAD (2.50 ± 0.20 nm), GSD (65.50 ± 5.50%), and (92.28 ± 0.2%) as shown in Table 3, signifying an e cient for drug delivery [49,50]. Moreover, the drug deposition study performed by Next Generation Impactor (NGI) showed the highest deposition for NAC-PLGA@Cs as compared to NAC-PLGA NPs at stage 3 followed by 4 and 5indicating the deep lung deposition of developed inhalable composites as shown in Fig.…”
Section: In Vitro Pulmonary Deposition Studysupporting
confidence: 56%
“…Some studies revealed that MMAD of 1-5µm could be optimal range particles size for pulmonary delivery [48]. In our study, obtained results suggested that developed PLGA composites showed an acceptable range of MMAD (2.50 ± 0.20 nm), GSD (65.50 ± 5.50%), and (92.28 ± 0.2%) as shown in Table 3, signifying an e cient for drug delivery [49,50]. Moreover, the drug deposition study performed by Next Generation Impactor (NGI) showed the highest deposition for NAC-PLGA@Cs as compared to NAC-PLGA NPs at stage 3 followed by 4 and 5indicating the deep lung deposition of developed inhalable composites as shown in Fig.…”
Section: In Vitro Pulmonary Deposition Studysupporting
confidence: 56%
“…Those bacteria may spread, if they are alive, through the lymphatic system or the circulation to the regional lymph nodes, the apex of the lung, kidneys, brain, and bony parts of the body, where TB sickness is most likely to develop. This process of dissemination sets the immune system for an expanded response (Figure 1D) [27]. To use an analogy, a bacterial jail called a granuloma aims to isolate a bacterium beneath an enclosure of immune cells.…”
Section: Tb Pathophysiologymentioning
confidence: 99%
“…In another study novel cospray dried RMP phospholipid lipospheres (SDRPL) to influence on RMP solubility and oral BA. [39] Solid-state techniques were employed to characterize the liposphere formulation. SDRPL solubility was determined in distilled water.…”
Section: Rifampicin (Rmp)mentioning
confidence: 99%